Economics of milkfish production in selected barangays in Hamtic, Antique. - Del Rosario, Eda Hope F.
This study on milkfish production in selected barangays in Hamtic, Antique was puposely conducted to generate information about the socio-economic characteristics and profitability of the milkfish production in Hamtic, Antique. An interview schedule was used to interview 68 respondents who were all engaged in milkfish production in Hamtic, Antique. Out of these respondents, 42 were identified as owner-operators who spent enough money to finance the daily expenses in all ponds' activities while the rest were caretakers who were responsible for all the hard works in the pond from stocking to harvesting even in preparing the pond, maintaining and repairing of dikes and canals., The study found out that milkfish farmers were composed not only of males but also of females despite of the fact that the activity requires too much physical strength. There were 55 males while females were only 13 to comprise the 68 respondents needed for the study. Furthermore, it was discovered that milkfish farmers were composed of married and single of the age ranging from 18 to 78 years old. All of the respondents have gone to school. About 30 of them reached and graduated college, 18 enrolled or graduated from high school while the remaining 20 attended and graduated from the elementary grades. The household size ranged from 3-15 members. With response to this, the data showed that with an average household size of 6, an ordinary low-income earner especially if his/her sole source of income is milkfish farming will have the difficulty to meet the basic needs of the family especially the school expenses of the children. Majority of the respondents' annual income ranges from P8,400 up to P60,000.00. Their primary source of income usually came from the ponds output, while others have ricefarming, fry gathering, employing in the government offices and other businesses like computer rentals, selling dry goods, hollow block factories, etc. as the source of their primary income. Secondary occupation on the other hand, were consist of ricefarming businesses, fry gathering and some were still the barangay council members of their respective barangays. Milkfish production in Hamtic, Antique was found out profitable. The pure economic profit of all the respondents was Php11,609.09 based on per hectare per cropping but only Php13.99 if based on per kilogram per hectare per cropping of milkfish produced. Most of the milkfish farmers in Hamtic, Antique believed that the major problem they encountered during the study period was flood. Stealing, marketing, lack of capital for the development of the pond and scavengers such as the so called "alinsawog" and "tugak" only follows.